2020
DOI: 10.35848/1347-4065/ab8b74
|View full text |Cite
|
Sign up to set email alerts
|

Four-terminal polycrystalline Ge1−x Sn x thin-film transistors using copper-induced crystallization on glass substrates and their application to enhancement/depletion inverters

Abstract: Polycrystalline germanium-tin (Ge 1−x Sn x ) thin films with a thickness of 15 nm were grown at 500 °C using Cu-induced crystallization. The films were applied to fabricate four-terminal (4T) thin-film transistors (TFTs) on a glass substrate. The top gate (TG) was fabricated from 30 nm thick SiO 2 , while the bottom gate (BG) consisted of a double layer of HfO 2 and SiO 2 with a capacitance equivalent thickness of 16 nm. Aluminuminduced lateral metallization of the source and drain (SD) was implemented to decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
(80 reference statements)
1
6
0
Order By: Relevance
“…There is no oxide compound signal of GeO x or SnO x in the Ge 3d and Sn3d 5/2 spectra [46], which is one of the reasons for the high mobility. As depicted in Figure 4b, the XRD analysis reveals that the GeSn layer is polycrystalline after annealing at 350 • C. The diffraction peaks related to GeSn are crystal orientations GeSn (111), GeSn (220), and GeSn (311), corresponding to 2θ values of 27.0 • , 45.0 • , and 52.7 • , respectively, which are similar to previously published data [29,[47][48][49]. Additionally, at 2θ = 30.79 • and 55.03 • , diffraction peaks of β-Sn (200) and β-Sn (301) were observed [22,49,50], which could be the Sn precipitated during the rapid thermal annealing at 350 • C. To thoroughly comprehend the fundamental physical properties related to the hole mobility of the GeSn pTFT, the electronic structure and hole effective mass were computed based on first principles.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…There is no oxide compound signal of GeO x or SnO x in the Ge 3d and Sn3d 5/2 spectra [46], which is one of the reasons for the high mobility. As depicted in Figure 4b, the XRD analysis reveals that the GeSn layer is polycrystalline after annealing at 350 • C. The diffraction peaks related to GeSn are crystal orientations GeSn (111), GeSn (220), and GeSn (311), corresponding to 2θ values of 27.0 • , 45.0 • , and 52.7 • , respectively, which are similar to previously published data [29,[47][48][49]. Additionally, at 2θ = 30.79 • and 55.03 • , diffraction peaks of β-Sn (200) and β-Sn (301) were observed [22,49,50], which could be the Sn precipitated during the rapid thermal annealing at 350 • C. To thoroughly comprehend the fundamental physical properties related to the hole mobility of the GeSn pTFT, the electronic structure and hole effective mass were computed based on first principles.…”
Section: Resultssupporting
confidence: 88%
“…This is the reason why GeSn has been proposed for pMOS or pTFT. However, the reported GeSn pTFTs in the literature suffered from poor I ON /I OFF [26][27][28][29], which is due to the leakage current of the small energy bandgap. Table 2 displays the crucial TFT device parameters of various poly-GeSn TFTs [26][27][28][29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…27) Therefore, we fabricated a poly-Ge (poly-Ge 1−x Sn x ) TFT using Cu-MIC and a DG structure on a glass and plastic substrate. [26][27][28] For the Cu-MIC DG poly-Ge 1−x Sn x TFTs crystallized at 500 °C, we achieved an I on /I off ratio of 1 × 10 4 on a glass substrate. 28) In this paper, we evaluated in-detail the crystalline quality of Cu-MIC poly-Ge films thinner than 15 nm crystallized at 400 °C using micro-Raman scattering, in-plane X-ray diffraction (XRD), transmission electron microscopy (TEM), TEM energy dispersive X-ray spectroscopy (TEM-EDX), and TEM electron diffraction (TEM-ED).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported on Cu-MIC and the superior performance of Cu-MIC poly Ge-based thin-film transistors. [22][23][24][25][26][27][28][29][30][31][32] Thus, Cu is very important as a catalyst for the crystallization of a-Ge in applications for semiconductor devices; however, research at the microscopic level has been insufficient. Therefore, we studied the dynamic crystallization process of a-Ge thin films containing Cu nanoparticles using in situ TEM.…”
mentioning
confidence: 99%